Narratives of Nostos by Italian-Canadian Women - Canton, Licia (Italian Canadiana, 2021)
We are privileged to read and write and share narratives of nostos that are inspired by our (grand)parents’ decision to emigrate. The return journey “home” shows a need to look to the past, towards one’s roots, in an attempt to better understand the present. This essay looks at representations of nostos in the Italian-Canadian literary community, with an emphasis on narratives by women who were born in Italy as well as those whose (grand)parents emigrated to Canada. To varying degrees, the discussion will touch on the works of established and emerging authors from Ontario, Quebec and Alberta.